2020
DOI: 10.1038/s41598-020-59164-3
|View full text |Cite
|
Sign up to set email alerts
|

Extract from used Xpert MTB/RIF Ultra cartridges is useful for accurate second-line drug-resistant tuberculosis diagnosis with minimal rpoB-amplicon cross-contamination risk

Abstract: (Ultra) detects Mycobacterium tuberculosis and rifampicin resistance. Follow-on drug susceptibility testing (DST) requires additional sputum. Extract from the diamond-shaped chamber of the cartridge (dCE) of Ultra's predecessor, Xpert MTB/RIF (Xpert), is useful for MTBDRsl-based DSt but this is unexplored with Ultra. Furthermore, whether CE from non-diamond compartments is useful, the performance of FluoroType MTBDR (FT) on CE, and rpoB cross-contamination risk associated with the extraction procedure are unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…In this review, 49 isolates with confirmed phenotypic RIF-resistance do not harbor any known mutation in the rpoB gene, which may be explained by the fact that RIF resistance-conferring mutations are present elsewhere in the rpoB gene (such as a V146F and I572F) [ 42 , 43 ], suggesting that the nature and frequency of mutations in the rpoB gene vary considerably, between different geographical regions [ 44 ], by the fact that not all the mutations are targeted by the probes used [ 45 ], or as it has been reported that molecular assays still have some drawbacks, such as product cross contamination which is a major problem leading to false positive results [ 20 ]. The reason for this cross contamination has not been elucidated properly [ 46 ], but it may be due to laboratory procedures (protocol for pretreatment, DNA extraction, and detection of the amplification product) [ 47 ]. Therefore, failure to detect RIF-resistance with rapid molecular tests (about 10% of cases in this study), added to the risk factors for unsuccessful TB treatment and MDR-TB development, could risk gains made in the fight against TB.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, 49 isolates with confirmed phenotypic RIF-resistance do not harbor any known mutation in the rpoB gene, which may be explained by the fact that RIF resistance-conferring mutations are present elsewhere in the rpoB gene (such as a V146F and I572F) [ 42 , 43 ], suggesting that the nature and frequency of mutations in the rpoB gene vary considerably, between different geographical regions [ 44 ], by the fact that not all the mutations are targeted by the probes used [ 45 ], or as it has been reported that molecular assays still have some drawbacks, such as product cross contamination which is a major problem leading to false positive results [ 20 ]. The reason for this cross contamination has not been elucidated properly [ 46 ], but it may be due to laboratory procedures (protocol for pretreatment, DNA extraction, and detection of the amplification product) [ 47 ]. Therefore, failure to detect RIF-resistance with rapid molecular tests (about 10% of cases in this study), added to the risk factors for unsuccessful TB treatment and MDR-TB development, could risk gains made in the fight against TB.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cartridges had to be punctured with a syringe to extract DNA. 22,23 A strength of this TB-Diskebased workflow is that, besides providing DNA for TB testing, a separate external reaction tube containing DNA for additional tests provides maximal flexibility; and no puncturing of the cartridge is required. After diagnosis of TB, Inh, Rif, and SLD resistance markers can be immediately investigated by PCR, LPA, or potentially targeted next-generation sequencing in a stepwise algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, workarounds using the Xpert MTB/Rif Ultra cartridges were considered for further use of the extracted DNA for downstream testing. 48,49 This involves puncturing of the cartridges with a syringe to recover the amplification product. In addition to the risk of injury from syringe handling, the DNA used from Xpert cartridges is already amplified, posing a serious risk of bias and high error rates in downstream analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, workarounds using the Xpert MTB/Rif Ultra cartridges were considered for further use of the extracted DNA for downstream testing. 48,49…”
Section: Discussionmentioning
confidence: 99%